USE OF SEXED BULLETIN SPERM AS A BIOTECHNOLOGICAL TOOL FOR INTENSIFYING DAIRY CATTLE REPRODUCTION - Pryshedko, Volodymyr; Halaktenov, Dmytro; Zaitseva, Oleksandra; Misnyi, Taras (European Science, 2025)
The article investigates the effectiveness of using sexed semen to improve reproductive performance in a Holstein dairy herd at an industrial farm in northern Ukraine. It was found that the average milk yield per cow over 305 lactation days was 9,435 kg,